Pelatihan Penggunaan Mesin Sablon Botol Untuk Pelaku UMKM Makanan Minuman Ringan Di Kota Pasuruan - Lestari Setyowati; Sari Kamina; Arif Sutrisno; Fariza Wahyu Arizal; Barotun Mabaroh (Altruis: Journal of Community Services, 2021)
One way to attract consumers to buy products is through attractive packaging. Therefore, this community service (SSI) aims to provide training related to packaging polishing using screen printing for small scale industry actors in the city of Pasuruan. Specifically, the purpose of writing this article is to describe the implementation and results of bottle screen printing training as a form of community service for food and beverage business actors in the city of Pasuruan. The method implemented is divided into three main stages, namely analysis as well as preparation, implementation, and evaluation. The team collaborated with the Demer sablon company, Pasuruan city to provide screen printing training materials. In the training session, many participants were enthusiastic about asking questions and greatly appreciated the training activities. Also, in the practice of screen printing, many participants produced good screen prints in the first trial (84%), while others (16%) produced ordinary screen prints. It can be concluded that community service activities through bottle screen printing training for SSI actors in the city of Pasuruan are very useful and increase the knowledge and basic skills of participants on how to screen print packaging bottles manually.